2014
DOI: 10.1007/s11269-014-0664-5
|View full text |Cite
|
Sign up to set email alerts
|

A Coupled Mathematical Model to Predict the Influence of Nitrogen Fertilization on Crop, Soil and Groundwater Quality

Abstract: Intensified use of nitrogen based fertilizers in agriculture has resulted in a significant increases in soils and groundwater nitrate concentrations all over the world. Here we propose a new coupled model which describes the physical transport and biogeochemical dynamics of the water and nitrogen compounds in a soil-water-plant-groundwater system. Our model takes into account water infiltration into an unsaturated porous medium, the complex biogeochemical cycle of nitrogen in soils, nitrate leaching from the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…At the same time, in order to assess the ecological component of the process of washing out the components of agrochemicals in a row layer, a number of researchers apply separate mathematical models based on experimental investigations carried out in groundwater wells [7,8]. The expediency of this method is based on the possibility of experimental fixation of water-soluble forms of substances in washing water.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the same time, in order to assess the ecological component of the process of washing out the components of agrochemicals in a row layer, a number of researchers apply separate mathematical models based on experimental investigations carried out in groundwater wells [7,8]. The expediency of this method is based on the possibility of experimental fixation of water-soluble forms of substances in washing water.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, in some stations the electrical conductivity is the most common type of pollutant in groundwater systems [25]. Fertilizers used in agriculture contain nitrate, ammonium, and organic nitrogen, and their excessive use causes nitrogen pollution due to mixing of agricultural drainage with groundwater [26]. The average value in nitrate measurements varied between 9-65 mg/L.…”
Section: The Average Electrical Conductivity Values Changedmentioning
confidence: 99%
“…The modelling system also indicated that implementation of best fertilizer management practices should be able to reduce and control the amount of nitrate-N leaching into the shallow groundwater in the study area. Marinov and Marinov [96] simulated biogeochemical dynamics of the water and N in the soil-plant system and flow of nitrate-N to the ground water by coupling a 1D water transfer model for the unsaturated soil, a biochemical N transformation model for the soil, and a 2D model for dispersion of N in the groundwater. Simulations with this model system suggested that high crop yields along with minimal N loading to soils and groundwater can be achieved by creating an optimal balance between the amount of fertilizers and water applied to crops as well as the amount of nitrate-N and water used by plants.…”
Section: Simulation Models For Studying Nitrate Pollution Of Water Bomentioning
confidence: 99%